Filling the gap: A Comprehensive Freshwater Network to Map Microplastics across Ecological Gradients in Argentina - Alfonso, María B.; Scordo, Facundo; Epele, Luis B.; Isobe, Atsuhiko; Akmentins, Mauricio S.; Albariño, Ricardo; Albarran, Katya K.; Allende, Luz; Andrade-Muñoz, Alan S.; Ansoar-Rodríguez, Yadira; Diaz, Boris Gaston; Yacelga Villavicencio, Naomi C. (Wiley, 2024)
The first comprehensive freshwater microplastics monitoring initiative is underway in South America, focusing on lakes, shallow lakes, reservoirs, streams, and rivers from Argentina. The project Monitoring and Analysis of Plastic Pollution in Aquatic Environments (MappA) aims to implement a standardized methodology to comprehensively understand microplastics’ presence, characteristics, and distribution within these water bodies.